2001
DOI: 10.1073/pnas.171460498
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 suppresses spontaneous tumor growth and inhibits activation of matrix metalloproteinase-9 and mobilization of vascular endothelial growth factor

Abstract: Growth of tumors and metastasis are processes known to require neovascularization. To ascertain the participation of the endogenous angiogenic inhibitor thrombospondin-1 (TSP1) in tumor progression, we generated mammary tumor-prone mice that either lack, or specifically overexpress, TSP1 in the mammary gland. Tumor burden and vasculature were significantly increased in TSP1-deficient animals, and capillaries within the tumor appeared distended and sinusoidal. In contrast, TSP1 overexpressors showed delayed tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
335
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 430 publications
(361 citation statements)
references
References 37 publications
21
335
0
5
Order By: Relevance
“…Therefore, even though the TSP-1-null/Pyt tumors had fewer blood vessels, these blood vessels were much larger compared to the wild-type Pyt tumors. Our findings at the 90 day time-point and results that we have published previously with this model [42] are in agreement with those of Iruela-Arispe's group who found that the vessel density did not change between the TSP-1-null/c-neu tumors and the c-neu wild-type tumors; however, the vessels were significantly larger in the TSP-1-null/c-neu mice [10].…”
Section: Blood Vessel Size and Areasupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, even though the TSP-1-null/Pyt tumors had fewer blood vessels, these blood vessels were much larger compared to the wild-type Pyt tumors. Our findings at the 90 day time-point and results that we have published previously with this model [42] are in agreement with those of Iruela-Arispe's group who found that the vessel density did not change between the TSP-1-null/c-neu tumors and the c-neu wild-type tumors; however, the vessels were significantly larger in the TSP-1-null/c-neu mice [10].…”
Section: Blood Vessel Size and Areasupporting
confidence: 93%
“…In summary, the TSP-1-null tumors were in general more advanced in malignancy than the wild type tumors. These results are similar to those obtained with the c-neu mouse, another murine transgenic model of breast cancer [10]. At 168 days, tumors from the TSP-1-null/c-neu mice were more than twice as big as the wildtype/c-neu tumors.…”
Section: Endogenous Tsp-1 Inhibits Tumor Growthsupporting
confidence: 86%
See 1 more Smart Citation
“…TSP-1 also inhibits the activity of matrix metalloproteinase-9 (MMP-9) (Ribatti et al, 1998;Rodriguez-Manzaneque et al, 2001). TSP-1 inhibits angiogenesis by binding to the CD36 receptor protein, which is present on the endothelial cell surface (Dawson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombospondin-1 (TSP1) is an angiogenesis inhibitor, 3 a multidomain protein that binds a variety of receptors, including integrins, CD36, integrin-associated protein, heparan sulfate proteoglycans and more. 4 TSP1 blocks angiogenesis via CD36, a receptor constitutively expressed in a subset of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%